PENERAPAN MANAJEMEN RISIKO PADA PABRIK KELAPA SAWIT (PKS) PTPN IV UNIT USAHA PABATU TAHUN 2015 - jumirsa hijriani; halinda sari lubis; eka lestari mahyuni (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT The workers at PTPN IV Unit Usaha Pabatu directly confronted with the production process during operational activities, so that the Occupational Health and Safety (OHS) is important, therefore, it needed the good of OHS risk management to get zero accident. The company has implemented OHS risk management but there are still found work accidents and occupational problems. This study described the results of hazard identification, risk assessment and occupational accidents control by using HIRAC method 2015. This research was descriptive research that describes the application of risk management in the palm oil mill. Technique of collecting data used in this study was assessment documents. The implementation of risk management at PTPN IV Unit Usaha Pabatu 2015 implemented by the independent risk management team at seven stations is sortation/ loading ramp station, sterilizier station, thresher station, pressan station, klarification station, kernel station, and boiler station. The implementation of risk management based on the results of HIRAC 2015 showed that there are in each station, yet according with government regulations No.50 tahun 2012, because risk assessment not rated objectively. The company has implemented the risk control like the compliance of work instructions, installation of OHS signs, fire extinguisher provision and the usage of personal protective equipment (PPE). It is regulated in accordance with government regulations No.50 tahun 2012. Based on the results of the study, OHS management is expected to conduct OHS training and to improve the socialization of OHS to the workers.